2018
DOI: 10.5205/1981-8963-v12i7a231360p2021-2030-2018
|View full text |Cite
|
Sign up to set email alerts
|

Evidências para a avaliação dos pés da pessoa com diabetes mellitus

Abstract: RESUMOObjetivo: identificar os critérios de avaliação dos pés da pessoa com Diabetes Mellitus. Método: revisão integrativa com busca nas bases de dados MEDLINE, LILACS, Cochrane, SCOPUS e biblioteca virtual SciELO, com delimitação temporal entre 2011 e 2017 e amostra final de 16 artigos categorizados em anamnese, avaliação da pele e anexos, avaliação neurológica, avaliação vascular, avaliação anatômica dos pés e autocuidado. Resultados: a maioria dos artigos foi de 2013, com nível de evidência II. A categoria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…It was found, based on the testimonies, that there was a lack of transmission about the guidelines, such as: monitor the water temperature (with the water temperature always below 37 °C) during foot hygiene to avoid burns due to reduced thermal sensitivity; socks should not contain seams to prevent excessive friction; inspect the inside of the shoes daily to detect the presence of objects that can hurt the feet with the help of a mirror, even because of the low visual acuity that can hinder self-inspection resulting from complications of DM or other causes; do not remove corns and calluses, because they must be evaluated and treated by the health team; orient about the use of heater or hot water bag to warm the feet; and do not use chemical agents or plasters to remove corns or calluses [16][17][18] . Furthermore, it was observed that one nurse did not provide orientation to her patients because of the high demand.…”
Section: Discussionmentioning
confidence: 99%
“…It was found, based on the testimonies, that there was a lack of transmission about the guidelines, such as: monitor the water temperature (with the water temperature always below 37 °C) during foot hygiene to avoid burns due to reduced thermal sensitivity; socks should not contain seams to prevent excessive friction; inspect the inside of the shoes daily to detect the presence of objects that can hurt the feet with the help of a mirror, even because of the low visual acuity that can hinder self-inspection resulting from complications of DM or other causes; do not remove corns and calluses, because they must be evaluated and treated by the health team; orient about the use of heater or hot water bag to warm the feet; and do not use chemical agents or plasters to remove corns or calluses [16][17][18] . Furthermore, it was observed that one nurse did not provide orientation to her patients because of the high demand.…”
Section: Discussionmentioning
confidence: 99%
“…Constatou-se, com os depoimentos, que houve carência na transmissão acerca das orientações, como: monitorar a temperatura da água (com a temperatura da água sempre abaixo de 37 °C) no decorrer da higiene dos pés para evitar queimaduras em razão da sensibilidade térmica diminuída; as meias não devem conter costuras para impedir atrito demasiado; inspecionar diariamente o interior do calçado para detectar presença de objetos que possam machucar os pés com auxílio de um espelho, até pela baixa acuidade visual que pode dificultar a autoinspeção resultante de complicações do DM ou por outra causa; não retirar calos e calosidades, pois devem ser avaliados e tratados pela equipe de saúde; orientar quanto ao não uso de aquecedor ou bolsa de água quente para aquecer os pés; e não usar agentes químicos ou emplastros para remover calos ou calosidades [16][17][18] .…”
Section: Discussionunclassified
“…The application 'Cuidando do pé' was the tool for data recording, classification and guidance to the evaluated patients. This application was developed at the Federal University of Alfenas which published its formulation steps [11]. To formulate a systematic anamnesis with correct orientations, the application takes into consideration age, gender, time of diagnosis, weight, height, blood glucose measurement at the time of the questionnaire, medications in use, personal history, classification regarding knowledge about foot care, and level of foot pain.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted at the Federal University of Alfenas, Brazil, the application 'Cuidando do pé' ('Care of the Foot'), which by means of agile methodologies implemented the indicators of the evaluation of diabetic foot recommended by the Ministry of Health, transforming them into an attractive and practical technological product, which is a useful tool for guiding health professionals in the process of evaluating the feet of people with DM and measuring the risk of diabetic foot [11].…”
Section: Introductionmentioning
confidence: 99%